2020
DOI: 10.1016/j.sjbs.2020.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical composition of Zilla spinosa Forssk. medicinal plants grown in Saudi Arabia in response to spatial and seasonal variations

Abstract: Extracts of different medicinal plants had been used to control several diseases in both traditional medicine and modern drugs. In the current study, we aimed to examine the changes in chemical composition of Zilla spinosa Forssk. plants collected from different habitats in Saudi Arabia in response to spatial and seasonal variations. Z . spinosa samples were collected from two different sites in Riyadh and Eastern regions in Saudi Arabia to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…3). Significant differences trends among seasons in the minerals concentrations were in accordance with the results of Kamel and El-Absy [21], Glavac et al [69] and Al-Qahtani et al [70], but an opposite tendency was found by Williams and Chadwick [71]. During the two seasons, Ca concentrations in the summer season were higher than in the winter season of H. boveanus plants.…”
Section: Plant Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…3). Significant differences trends among seasons in the minerals concentrations were in accordance with the results of Kamel and El-Absy [21], Glavac et al [69] and Al-Qahtani et al [70], but an opposite tendency was found by Williams and Chadwick [71]. During the two seasons, Ca concentrations in the summer season were higher than in the winter season of H. boveanus plants.…”
Section: Plant Analysissupporting
confidence: 87%
“…4). Similarly, results were reported by Gonzalez-Hernandez et al [77] for crude protein, by Pouris et al [78] for proline and by Al-Qahtani et al [70] for total carbohydrates.…”
Section: Plant Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Due to the extreme climatic conditions, plants are forced to maintain increased levels of compounds with defensive activities as a survival mechanism against excessive oxidative stress Khalaf Allah et al) [2], bacterial infection, and animal grazing invasion. Plant secondary metabolites (PSM) are compounds like these (Al-Qahtani et al) [3], Youssef et al) [4]. For millennia, the knowledge of how to use plants medicinally has been passed down from generation to generation, and it has evolved based on observations, experience, and trial and error tests (Karunamoorthi et al) [5],…”
Section: Introductionmentioning
confidence: 99%
“…The entire plant has been used to treat hypertension [ 26 ]. Zilla spinosa has a long history of treating urinary and gallbladder stones [ 27 ] in this area of the region and has a purgative action [ 26 ].…”
Section: Introductionmentioning
confidence: 99%